EFFECTS OF SIZE, PROFITABILITY, AND GROWTH RATE TOWARDS CAPITAL STRUCTURE - Agus Munandar (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2014)
This study was aimed to examine the influence of size, profitability, and growth rate toward capital structure. Our sample includes companies which were belonged to Consumer Goods Industry and Miscellaneous Industry listed in Indonesia Stock Exchange (IDX) on the year period 2009-2014. We utilize panel data regression analysis and show that the capital structure (proxied by the total debt ratio)of the companies is positively determined by their size (proxied by the total revenue). The results of the analysis also showed that capital structure is also positively determined by profitability (proxied by the return on equity), but negatively determined by their growth rate (proxied by the asset growth rate). These findings are consistent with the previous literature. Key Words: Capital Structure, Debt to Equity Ratio, Panel Data, Indonesia